Facial mimetic, cosmetic, and functional standardized assessment of the facial artery musculomucosal (FAMM) flap. Issue 2 (April 2017) - Jowett, Nathan; Hadlock, Tessa A.; Sela, Eyal; Toth, Miklos; Knecht, Rainald; Lörincz, Balazs B.
Abstract: Objective: To objectively assess donor site morbidity after harvesting the facial artery musculomucosal flap. Use of the FAMM-flap in oral cavity reconstruction remains sporadic. This case series describes our newly developed standardized assessment of this flap in a floor of mouth (FOM) reconstructive setting. Methods: Standardized postoperative assessment of the FAMM flap for donor site wound complications, functional, facial mimetic and oncologic outcomes. Results: There were no wound complications. Oral competence remained intact, tongue mobility was good to excellent, average word articulation score was 98%, and mimetic function excellent in all patients. Three patients experienced ipsilateral upper lip anesthesia, and five patients were noted to have slight dysfunction of the orbicularis oris resulting in a loss of lip height at rest. Conclusion: The FAMM flap is a reliable option for reconstruction of ablative defects of the FOM, and should be considered a workhorse flap for oral cavity defects. Unlike the submental island flap, a complete level I dissection may be concurrently performed without compromising the vascular supply to the FAMM flap.